MASA DEPAN USAHA KONTER PULSA DI ERA DIGITAL - Teguh Permana; Andriani Puspitaningsih; Asri Djauhar; Surianti Surianti (MANAJEMEN, 2022)
This study aims to determine the future of the pulse counter business in the digital era. The method used is descriptive by collecting data directly in the field and analyzed. The results of the study indicate that there have been many pulse counter businesses that have replaced businesses or combined with other types of businesses. The implication of this is that the pulse counter business can no longer be relied on as a prospective business because other alternatives have emerged that can be used to buy credit either through mobile banking or e-commerce on the Internet